2010
DOI: 10.1136/pgmj.2009.094904
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous bidirectional endoscopy for iron deficiency anaemia: is it appropriate for patients under 50?

Abstract: Our findings suggest that synchronous BDE is an appropriate means of investigation for iron deficiency anaemia in patients >50 and for men <50 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In other words, the study did not provide an obvious answer to the question of the preferred investigation strategy in asymptomatic young men with IDA. A British study reported that significant GI findings were frequent in young men (< 50 years) with IDA (20.6%, 6/29) and suggested that endoscopy is an appropriate strategy of investigation for men < 50 years of age with IDA [ 24 ]. However, these two studies did not compare the prevalence of GI lesions between subjects with versus without IDA and reported only the proportion of GI lesions in young men with IDA.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the study did not provide an obvious answer to the question of the preferred investigation strategy in asymptomatic young men with IDA. A British study reported that significant GI findings were frequent in young men (< 50 years) with IDA (20.6%, 6/29) and suggested that endoscopy is an appropriate strategy of investigation for men < 50 years of age with IDA [ 24 ]. However, these two studies did not compare the prevalence of GI lesions between subjects with versus without IDA and reported only the proportion of GI lesions in young men with IDA.…”
Section: Discussionmentioning
confidence: 99%
“…To guide our recommendations, we aimed to assess the benefits and harms of bidirectional endoscopy. Because we could not identify any study, randomized or nonrandomized, that compared bidirectional endoscopy with observation or oral iron therapy alone in patients with IDA in any population group, we identified the following indirect evidence to assist the Panel in making decisions: we identified systematic reviews that evaluated the benefits of screening colonoscopy to no endoscopic evaluation 45,46 ; we identified observational cohort and cross-sectional studies to assess the frequency (or "diagnostic yield") of finding gastrointestinal tract lesions, and most importantly malignancy, during bidirectional endoscopy in patients with IDA [15][16][17][18][19][20]42,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] ; we identified studies that evaluated the rates of complications of gastrointestinal endoscopy [67][68][69][70][71][72] ; and we used the available epidemiologic reports to model the expected benefit and harm of bidirectional endoscopy for the different age/sex groups (Table 4). 73,74…”
Section: Bidirectional Endoscopy In Patients With Iron Deficiency Anemiamentioning
confidence: 99%
“…Bidirectional endoscopy detected lower gastrointestinal malignancy in 8.9% (95% CI, 8.3-9.5) and upper gastrointestinal malignancy in 2.0% (95% CI, 1.7-2.3) of largely men and postmenopausal women with IDA. 15,20,[47][48][49][51][52][53][54][55][56][60][61][62]65,66 It should be emphasized that this estimate is likely an overestimation due to the inclusion of some symptomatic patients in the reported cohorts (high risk of bias), which makes the exact baseline risk for malignancy in IDA uncertain in this risk group. Based on the available data, we have high certainty in the evidence that the risk of malignancy is many fold higher (up to 100-fold) than an average risk screening population of similar age.…”
Section: Evidence Supporting Bidirectional Endoscopy In Postmenopausamentioning
confidence: 99%
“…Furthermore, despite the lack of evidence, the BSG guidelines recommend that young men (< 50 years old) with IDA should be investigated in the same manner as older men [3]. This recommendation is weakly supported by the few published studies, which have confirmed the infrequent presence of any significant lower GI pathology in young men with IDA [50][51][52]. A recent study compared colonoscopy findings in young patients (both male and female, aged 40-49 years) to the average-risk of individuals aged 50-54 years undergoing colonoscopy.…”
Section: Lower Endoscopymentioning
confidence: 99%